Proximal Tibial Osteosarcoma in Pediatric Patient: A Case Report - Sandiwidayat, Komang Septian; Febyan, Febyan (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: The most frequent primary malignant bone tumor in children is osteosarcoma. Patients with osteosarcoma are currently treated with a combination of neoadjuvant and adjuvant chemotherapy as well as surgery, either limb-sparing surgery or limb-ablation surgery. How to manage the remaining bone growth during the limb-sparing procedure in youngsters is one of the challenges. Unfortunately, amputation is still many perform for OS patients. The purpose of this study was to inform and educate doctors about the value of early OS diagnosis and treatment in pediatric patients.Case Presentation: We presented case from a male 16 years old Balinese complaint of pain on her left knee 12 months ago. The pain was continuous and got worse at night. The patient went to a traditional masseuse and was given topical herbal ointment. Three months later, a lump appeared on her knee at the size of a small ball and getting bigger. We did a review slide of the previous biopsy sample by the pathology of anatomy in our hospital. The result came out as osteosarcoma with osteoblastic cells. We performed to amputated the limb-affected tumor following wound care routinely controlled.Results: Intraoperatively, we performed wide excision, without patellar tendon, medial collateral ligament, and cruciate ligament preserve. We amputated the limb-affected tumor. The patient routinely controlled to our outpatient clinic every week. Unfortunately, the patient was died after 3 weeks of admission.Conclusion: To reduce the risk of misdiagnosis or delayed diagnosis of osteosarcoma, every source of knee pain with a mass in pediatric age groups should be thoroughly explored with a high index of suspicion for malignant lesions. Therefore, amputation is a cutting-edge osteosarcoma treatment that can be avoided if the patient can be identified early and treated quickly in pediatric oncology malignant instances.Keywords: osteosarcoma, long bone, diagnosis, tibia, pediatricCorrespondence: Komang Septian Sandiwidayat. Oncology Division, Department of Orthopaedic & Traumatology, Sanglah General Hospital, Faculty of Medicine, Udayana University, Bali, Indonesia. Email: drseptianortho@gmail.com. Mobile: 62-821-4725-2042.Indonesian Journal of Medicine (2022), 07(03): 298-305https://doi.org/10.26911/theijmed.2022.07.03.06